2023
DOI: 10.3390/ani13060992
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Candidate Genes and Functional Pathways Associated with Body Size Traits in Chinese Holstein Cattle Based on GWAS Analysis

Abstract: Body size is one of the most economically important traits of dairy cattle, as it is significantly associated with cow longevity, production, health, fertility, and environmental adaptation. The identification and application of genetic variants using a novel genetic approach, such as genome-wide association studies (GWASs), may give more insights into the genetic architecture of complex traits. The identification of genes, single nucleotide polymorphisms (SNPs), and pathways associated with the body size trai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 63 publications
0
1
0
Order By: Relevance
“…Body weight phenotype in Morada Nova sheep using a similar threshold line (-Log 10 P 3 ). Abdalla et al (2023) identified two SNP markers in the BTA1 of Chinese Holstein cattle, ARS-BFGL-NGS-18743 (MYH15 gene) and BTB-00074122, which were substantially related to body height and body depth, respectively. Furthermore, two SNP markers in BTA1, ARS-BFGL-NGS-98203 and ARS-BFGL-NGS-115015, were found to be strongly linked with age at first calving in Hanwoo heifers (Hyeong et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Body weight phenotype in Morada Nova sheep using a similar threshold line (-Log 10 P 3 ). Abdalla et al (2023) identified two SNP markers in the BTA1 of Chinese Holstein cattle, ARS-BFGL-NGS-18743 (MYH15 gene) and BTB-00074122, which were substantially related to body height and body depth, respectively. Furthermore, two SNP markers in BTA1, ARS-BFGL-NGS-98203 and ARS-BFGL-NGS-115015, were found to be strongly linked with age at first calving in Hanwoo heifers (Hyeong et al, 2014).…”
Section: Discussionmentioning
confidence: 99%